Tertiary α‐Silyl Alcohols by Diastereoselective Coupling of 1,3‐Dienes and Acylsilanes Initiated by Enantioselective Copper‐Catalyzed Borylation - Feng, Jian‐Jun; Oestreich, Martin (Angewandte Chemie International Edition, 2019)
An efficient synthesis of functionalized tertiary α‐silyl alcohols by an enantio‐ and diastereoselective copper‐catalyzed three‐component coupling of 1,3‐dienes, bis(pinacolato)diboron, and acylsilanes is reported. The reaction proceeds well with different 1,3‐dienes and a broad range of aryl‐ as well as alkenyl‐ but also alkyl‐substituted acylsilanes. The target compounds are formed with high regio‐, diastereo‐, and enantioselectivity (up to 99 % ee and d.r. >20:1) and are highly versatile synthetic building blocks. All at once: A copper‐catalyzed three‐component coupling of 1,3‐dienes, bis(pinacolato)diboron, and acylsilanes affords densely functionalized tertiary α‐silyl alcohols regioselectively in high yields as well as with excellent enantioselectivity (up to 99 % ee) and diastereoselectivity (d.r. >20:1). Subsequent transformations illustrate the versatility of these chiral building blocks.